English Vocabulary Knowledge at the End of Compulsory Education in Iceland: Exploring Receptive and Productive English Vocabulary in Relation to Extramural Activities among 10th Grade Students in Iceland - Lára Marta Fleckenstein 1979- (2018)
The focus of this study was to examine the receptive and productive level of vocabulary students have acquired at the final year of compulsory education in Iceland and to explore how high and low scoring students are using English differently. In addition, the study aimed to examine the relationship between students’ receptive and productive vocabulary and to determine what kind of vocabulary students use in written production. Finally, the study explored how much time they in spend on various extramural English activities. To achieve these goals 75 participants attending 10th grade in Iceland were asked to complete two proficiency tests, a background questionnaire, write a written sample and fill out a language diary. The study’s main findings reveal that students by the end of compulsory education in Iceland generally have acquired adequate amount of receptive high frequency vocabulary and many students have acquired a considerable amount of mid frequency vocabulary. However, students productive vocabulary knowledge is generally lacking at all tested frequency levels. This was also obvious in students written samples as they mostly used high frequency vocabulary, although the texts of the higher scoring students were more diverse. Furthermore, findings show a strong relationship between receptive and productive vocabulary knowledge, demonstrating that one can predict the other. The study also revealed that participants spend an enormous amount of time on extramural English activities. Finally, when comparing the highest and lowest scoring participants from the vocabulary level tests it was clear that the students that had acquired a large amount of vocabulary estimated their language skills higher, they were more positive towards the language, wrote longer and more diverse texts and spent much more time in contact with extramural English activities than the students who had acquired the smallest amount of vocabulary.